Endoglin in human liver disease and murine models of liver fibrosis—A protective factor against liver fibrosis. (23rd October 2017) - Alsamman, Muhammad; Sterzer, Viktor; Meurer, Steffen K.; Sahin, Hacer; Schaeper, Ute; Kuscuoglu, Deniz; Strnad, Pavel; Weiskirchen, Ralf; Trautwein, Christian; Scholten, David
Abstract: Background & Aims: Liver fibrosis is the outcome of chronic liver injury. Transforming growth factor‐β (TGF‐β) is a major profibrogenic cytokine modulating hepatic stellate cell (HSC) activation and extracellular matrix homeostasis. This study analyses the effect of Endoglin (Eng), a TGF‐β type III auxiliary receptor, on fibrogenesis in two models of liver injury by HSC‐specific endoglin deletion. Methods: Eng expression was measured in human and murine samples of liver injury. After generating GFAP Cre(+) Eng Δ HSC mice, the impact of Endoglin deletion on chronic liver fibrosis was analysed. For in vitro analysis, Eng flox/flox HSCs were infected with Cre‐expressing virus to deplete Endoglin and fibrogenic responses were analysed. Results: Endoglin is upregulated in human liver injury. The receptor is expressed in liver tissues and mesenchymal liver cells with much higher abundance of the L‐Eng splice variant. Comparing GFAP C re(−) Eng f/f to GFAP C re(+) Eng Δ HSC mice in toxic liver injury, livers of GFAP C re(+) Eng Δ HSC mice showed 39.9% ( P  < .01) higher Hydroxyproline content compared to GFAP C re(−) Eng f/f littermates. Sirius Red staining underlined these findings, showing 58.8% ( P  < .05) more Collagen deposition in livers of GFAP C re(+) Eng Δ HSC mice. Similar results were obtained in mice subjected to cholestatic injury. Conclusion: Endoglin isoforms are differentially upregulated in liver samples of patients with chronic and acute liver injury. Endoglin deficiency in HSC significantly aggravates fibrosis in response to injury in two different murine models of liver fibrosis and increases α‐SMA and fibronectin expression in vitro. This suggests that Endoglin protects against fibrotic injury, likely through modulation of TGF‐β signalling.